Late Middle Kingdom at Qubbet el-Hawa: The Case of QH 35n - Bardoňová, Martina; Guimarey Duarte, Rosario; Alemán Aguilera, Inmaculada; Rubio Salvador, Ángel; Botella López, Miguel Cecilio; Jiménez Serrano, Alejandro (Mitteilungen des Deutschen Archäologischen Instituts Kairo, 2024)
The present paper concerns the use of one of the well-known ›nomarchal‹ necropoleis, Qubbet el-Hawa, west of modern Aswan, during the locally less explored era of the late Middle Kingdom, subsequent to Amenemhat III. The subject of this article is a multidisciplinary analysis of a group of burials dated between the late 12ᵗʰ and mid-13ᵗʰ Dynasties, recently discovered in a reused monument, tomb QH 35n. The main aim is to present these new finds in their archaeological, spatial, and temporal contexts, in order to understand by whom and in which way the ancient necropolis was used and reused during the late Middle Kingdom.